The myeloid cell-driven transdifferentiation of endothelial cells into pericytes promotes the restoration of BBB function and brain self-repair after stroke - Tingbo Li; Ling Yang; Jiaqi Tu; Yufan Hao; Zhu Zhu; Yingjie Xiong; Qingzhu Gao; Lili Zhou; Guanglei Xie; Dongdong Zhang; Xuzhao Li; Yuxiao Jin; et al. (eLife)
Ischemic stroke, one of the leading causes of death in the world, is accompanied by the dysfunction of the blood-brain barrier (BBB), which aggravates neuron damage. However, the mechanisms underlying the restoration of BBB in the chronic stage after stroke remain unclear. Here, pericyte pool alterations and their consequences for BBB integrity and brain recovery were analyzed in the C57BL/6 mice stroke model. Lineage tracing, RNA-seq, and immunofluorescence staining revealed endothelial cell (EC) transdifferentiation into pericytes (E-pericytes) in C57BL/6 mice after stroke. E-pericytes depletion by diphtheria toxin A (DTA) aggravated BBB leakage and exacerbated neurological deficits in the MCAO model. The myeloid cell-driven transdifferentiation of ECs into pericytes accelerated BBB restoration and brain self-repair after stroke via endothelial-mesenchymal transformation (EndoMT). Decreasing the number of E-pericytes by specific knockout of the Tgfbr2 gene in ECs also aggravated BBB leakage and exacerbated neurological deficits. EC-specific overexpression of the Tgfbr2 gene promoting E-pericytes transdifferentiation reduced BBB leakage and exerted neuroprotective effects. Deciphering the mechanism by which E-pericytes coordinate post-stroke recovery may reveal a novel therapeutic opportunity.